Rappresentazioni sentimentali dell’infanzia - Giallongo, Angela (Studi sulla Formazione/Open Journal of Education, 2011)
This report examines, among the paradigms that emerged in the last thirty years of research, studies that have shown very significant phenomenon of the past, namely the emotional relationships (representations and practices) in the first years of life. The author makes a reflection on this theme from Middle Ages and she highlights both the negative behaviors related to childhood but also positive ones, denying in part the positions too uncompromising Aries. We must ask ourselves: is this still valid point of view that Western culture has been emancipated from the barbaric medieval feel only when it starts to make a loving sense of protection to children? The author gives us her interpretation.